TECNOESTRÉS Y EDAD: UN ESTUDIO TRANSVERSAL EN TRABAJADORES PÚBLICOS. - Sánchez-Gómez, Martin; Cebrián, Bryan; Ferré, Paula; Navarro, Mónica; Plazuelo, Nerea (Panamerican Journal of Neuropsychology / Cuadernos de Neuropsicología)
Despite the findings on stress and technology, the relationship between age and techno-stress in public workers is still limited. The main aim of this study was to observe the relationship between age and techno-stress in officials of different Spanish municipalities. The cross-sectional study was carried out in 132 workers (60 men and 72 women) with a mean age of 42.9 years (SD: 9.49). To assess techno-stress, the RED Questionnaire was administered. Correlation analyzes reveal that age is positively related to techno-fatigue and negatively to techno-addiction. Furthermore, the MANOVA test indicates significant differences between baby boomers and generation Y. In summary, these results support the idea that older public workers are more prone to technology-related stress at work. Despite this, more research should be done to support these findings.